Characteristics of Startup Company and Its Strategy: Analysis of Indonesia Fashion Startup Companies - Nurcahyo, Rahmat; Ilhamsyah Akbar, Mohammad; Sihono Gabriel, Djoko (International Journal of Engineering and Technology, 2018)
Startup companies, as an organization in the early phase, have different characteristics than mature organization. The research method is qualitative because the purpose is trying to understand the startup characteristics. The research object is Indonesia fashion startup companies because it is one of the most promising start ups in Indonesia. Strategy choices are crucial in fashion startups in Indonesia. Objective of this paper is to analyze the strategy that has been used in fashion startups in Indonesia. Most of the startups use intuitive decision making. The result is most fashion startups tend to use intensive strategy because the market is still growing. Intensive market penetration through marketing strategy and related diversification are the two strategies that commonly used in fashion startups in Indonesia.Â Â
Keywords: Fashion; Startup; Strategy; Intensive Strategy.